Anxiety level and risk factors among pediatric patients in endoscopic procedures outside the operating room: A cross-sectional study - Arıcan, Şule; Yücel, Aylin; Yılmaz, Resul; Hacıbeyoğlu, Gülçin; Yusifov, Merve; Yüce, Sait; Topal, Ahmet (Journal of Surgery and Medicine, 2020)
Aim: Endoscopy under anesthesia creates stress and anxiety in children and their parents. In this study, we aimed to determine the preoperative anxiety levels of parents and patients who were routinely informed before endoscopy and examine the relationship between children and parents' state and trait anxiety levels. Methods: A cross-sectional study was planned in which pediatric patients and parents were included. The study comprised 104 ASA I-II patients, aged 6-14 years, who were scheduled for endoscopy under deep sedation, and their parents. Immediately after the child patient was taken to the treatment room, parents were asked to fill out the State-Trait Anxiety Inventory. The demographic characteristics of the patients were recorded. The children’s anxiety level immediately after separation from parents was evaluated with Modified Yale Preoperative Anxiety Scale (m-YPAS). The patients were divided into two groups according to anxiety levels. Those with m-YPAS >30 were considered the anxiety (+) group, m-YPAS ≤30 were defined as the anxiety (-) group. Results: The mean age of the patients was 11.8 (2.6) years (6-14). Twenty-nine patients had m-YPAS> 30, and 75 patients had m-YPAS ≤30. Parent anxiety levels were not significantly different between the two groups. There was a strong negative correlation (r=-0.589, P<0.001) between child’s anxiety and child age, a negative moderate correlation between child’s anxiety and parent age (r=-0.259, P=0.008), and weak positive correlation between child’s anxiety and complications (r=0.218, P=0.026). Young age was determined as an independent risk factor for increased child anxiety (OR: 0.501, P<0.001, 95% CI: 0.390-0.643). Conclusion: There is no relationship between preoperative anxiety in school-age children and parental anxiety. Young age is an independent risk factor for the development of anxiety in the child.